2007
DOI: 10.1016/j.virol.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 integrates into resting CD4+ T cells even at low inoculums as demonstrated with an improved assay for HIV-1 integration

Abstract: Human Immunodeficiency Virus Type 1 (HIV-1) establishes a latent reservoir early in infection that is resistant to the host immune response and treatment with highly active antiretroviral therapy (HAART). The best understood of these reservoirs forms in resting CD4(+) T cells. While it remains unclear how reservoirs form, a popular model holds that the virus can only integrate in activated CD4(+) T cells. Contrary to this model, our previous results suggest that HIV-1 can integrate directly into the genomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 68 publications
13
138
0
Order By: Relevance
“…2B). The slope coefficients close to 0.1 revealed that the absolute number of integrated copies measured in the repetitive-sampling strategy is 10-fold lower than the expected number in the integration standard; this fold difference is stable at all dilution points assessed and is consistent with published data showing that 10% of integration events are detected (16,17 ). A third standard curve with higher numbers of integrated copies was run to assess the upper limit of positive to negative wells in the 42-replicate setup.…”
Section: Assessment Of the Poisson Methods By Use Of The Standard Dilusupporting
confidence: 88%
See 3 more Smart Citations
“…2B). The slope coefficients close to 0.1 revealed that the absolute number of integrated copies measured in the repetitive-sampling strategy is 10-fold lower than the expected number in the integration standard; this fold difference is stable at all dilution points assessed and is consistent with published data showing that 10% of integration events are detected (16,17 ). A third standard curve with higher numbers of integrated copies was run to assess the upper limit of positive to negative wells in the 42-replicate setup.…”
Section: Assessment Of the Poisson Methods By Use Of The Standard Dilusupporting
confidence: 88%
“…Sorting of green fluorescent protein (GFP)-positive cells resulted in a population of cells with 1 proviral copy per cell (15)(16)(17). Peripheral blood mononuclear cells were isolated from 56 HIVinfected patients by density gradient centrifugation and frozen to Ϫ80°C at a cooling rate of 1°C/min in 90% fetal calf serum with 10% DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although researchers do employ patient samples, when doing so, MHC mismatched CD4ϩ T cells are typically added to the cultures to allow expansion of the virus, so it is unclear whether allogeneic reactivity might contribute to virus activation. Viral particles enveloped with the CXCR4-tropic envelope integrate into the genomes of resting CD4 ϩ T cells and result in a latent infection, as early as 3 days after infection, which can be reactivated by various stimuli including IL-7 and CD3/CD28 stimulation (32)(33)(34)(35). PBMCs from whole blood were isolated by Ficoll gradient centrifugation and then subjected to negative selection to isolate resting CD4 ϩ T cells.…”
Section: Av6 Activated Latent Hiv In Primary Cells Without Inducing Cmentioning
confidence: 99%